Reducing School Dropout in Madagascar through Policy and Community Interventions - Emynorane, Ralaivao Hanginiaina; Sulla, Razafitahindraza Erica Feyzine; Michel, Rakotoniriana Noelisoa Jean (RUANG KOMUNITAS: Jurnal Pengabdian Masyarakat, 2026)
This study aims to examine strategies to reduce school dropout in Madagascar through policy interventions and community involvement. School dropout remains a significant challenge influenced by socioeconomic constraints, weak school environments, and gaps between policy design and local implementation. This research employs a qualitative approach, with data collected from 10 key informants consisting of school leaders, teachers, local authorities, and community representatives selected through purposive sampling. Thematic analysis is used to identify key patterns related to the causes of dropout and effective intervention strategies. The findings indicate that poverty, inadequate infrastructure, and limited educational resources contribute to low student engagement, while weak policy enforcement reduces the effectiveness of existing reforms. On the other hand, strong community participation, including the involvement of parents and local governance systems, plays an important role in supporting students’ educational continuity. This study emphasizes that alignment between policy and community-based practices can enhance the sustainability and effectiveness of dropout reduction efforts. It recommends strengthening policy implementation, improving school environments, and increasing active community engagement. Future research is suggested to examine the long-term impact of interventions across different regions in Madagascar.